Towards conductive-gel-free electrodes: Understanding the wet electrode, semi-dry electrode and dry electrode-skin interface impedance using electrochemical impedance spectroscopy fitting - Li, Guangli; Wang, Sizhe; Duan, Yanwen Y. (Sensors and actuators. B, Chemical, 2018)
•Equivalent circuit models for three typical EEG electrodes were proposed.•Area-normalized impedance was used throughout the whole analysis.•Impedance fitting with mild pressure and skin abrasion conditions were investigated.•Inspiration for development of novel conductive-gel-free electrodes was discussed. The electrode-scalp impedance of six subjects is studied by electrochemical impedance spectroscopy using three representative electrodes, namely wet electrodes, semi-dry electrodes, and dry electrodes. With the analysis of proposed equivalent models and area-normalized impedance (kΩ cm2), the specific electrode double layer resistances are 530 Ω cm2 for all electrodes, their specific contact resistances Res are 80 Ω cm2, 114 Ω cm2 and 20,077 Ω cm2, and their specific skin resistances Rs are 867 Ω cm2, 1730 Ω cm2 and 46,145 Ω cm2 for these three representative electrodes respectively. When pressure was applied on dry electrodes, Res reduced by 47% and Rs reduced by 81%. When pressure was applied on semi-dry electrodes, Rs reduced by 50% (Res is not applicable for semi-dry electrodes). After application of scalp abrasion for dry electrodes, Res reduced by 36% and Rs reduced by 82%. After application of scalp abrasion for semi-dry electrodes, Rs reduced by 64%. Seeking novel interface materials may break through the bottleneck for dry electrodes development in terms of integrated materials, mechanical support and electronic circuitry, while semi-dry electrodes have much development space to meet a balance of quick setup, comfortable wear, and satisfactory signal quality in many medical and out-clinic applications.